The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1111/jam.15414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of planktonic bacterial communities indoor and outdoor of aquaculture greenhouses

Abstract: Aims: Greenhouses are widely used in agriculture systems to shield crops from unfavourable weather to achieve a year-round food supply. In recent years, aquaculture ponds have been placed in greenhouses in many regions. The impacts of the greenhouses on planktonic bacterial communities should be uncovered. Methods and Results:In this study, two polyolefin film greenhouses accommodating aquaculture ponds were established and planktonic bacterial communities were compared from samples taken in aquaculture ponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Sequencing technology has revealed the bacterial taxa and predicted functions of the microbiota in aquaculture environments, as well as the effects on the growth and development of aquatic organisms (Caporaso et al 2011;Choudhury et al 2021). For example, Zhao et al (2022) found that planktonic bacterial communities differed between indoor and outdoor conditions in aquaculture greenhouses. Arias et al (2006) found that bacterial communities in a catfish aquaculture setting varied from pond to pond at a given time point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing technology has revealed the bacterial taxa and predicted functions of the microbiota in aquaculture environments, as well as the effects on the growth and development of aquatic organisms (Caporaso et al 2011;Choudhury et al 2021). For example, Zhao et al (2022) found that planktonic bacterial communities differed between indoor and outdoor conditions in aquaculture greenhouses. Arias et al (2006) found that bacterial communities in a catfish aquaculture setting varied from pond to pond at a given time point.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al. (2022) found that planktonic bacterial communities differed between indoor and outdoor conditions in aquaculture greenhouses. Arias et al .…”
Section: Introductionmentioning
confidence: 99%